Determination of the functional state of the vestibular analyzer volleyball players 14–15 years under the influence of a specially-designed exercises - Моісеєнко Олена Костянтинівна, (Olena Moiseyenko); Горчанюк Юрій Андрійович, (Yurii Gorchanyuk); Горчанюк Валерій Андрійович, (Valerii Gorchanyuk) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: indicators of a functional condition of the vestibular analyzer and their changes under the influence of specially directed exercises at volleyball players of 14–15 years old are given in the article. Results: the carried-out analysis of a functional condition of the vestibular analyzer, both before, and after rotary loadings to the pedagogical experiment testifies to insufficient development of a vestibular function of young volleyball players. Conclusions: the comparison of results of the studied groups after the introduction in the educational-training process of special exercises directed on the improvement of operation of the vestibular analyzer revealed considerable changes of indicators of volleyball players of the experimental group.